Y = X (sq Root 5x - 1)

Anonymous

From: -
Posts: -
Votes: -
Y = x (sq root 5x - 1)

 

Answer No.1

GamerMath

From: US
Posts: 26
Votes: 26
Dy = (15x - 2)/(2 square root (5x-1))

Answer No.2

Anonymous

From: -
Posts: -
Votes: -
Y = x (sq root of 5x - 1) dy/dx = (sq root of 5x - 1) + (x/2)*5/(sq root of 5x - 1) dy/dx = (sq root of 5x - 1) + (5x)/[2(sq root of 5x - 1)] dy/dx = [2(5x-1) + 5x]/[2(sq root of 5x - 1)] [ it is like √a + (1/√a) = [a+1]/√a] dy/dx = [15x-2]/[2(sq root of 5x - 1)]

Answer No.3

Anonymous

From: -
Posts: -
Votes: -
Y = x (sq root of 5x - 1) dy/dx = (sq root of 5x - 1) + (x/2)*5/(sq root of 5x - 1) dy/dx = (sq root of 5x - 1) + (5x)/[2(sq root of 5x - 1)]

Answer No.4

Anonymous

From: -
Posts: -
Votes: -
Dy/dx = (sq root 5x - 1) + x * 5/(2sqrt(5x-1))

Your Comment/Solution

Post As: Anonymous [Change]
Enter